Establishment of human immortalized mesenchymal stem cells lines for the monitoring and analysis of osteogenic differentiation in living cells. Issue 10 (October 2020) - Narai, Takashi; Watase, Ryohei; Nakayama, Yuji; Kodani, Isamu; Inoue, Toshiaki; Kokura, Kenji
Abstract: Mesenchymal stem cells (MSCs) are expected to be useful in bone regeneration treatment for various diseases and conditions, including cleft lip and palate, fracture, and bone absorption. However, to date, MSCs have failed to produce satisfactory results in clinical settings. This is primarily due to the low rate of induced osteogenic differentiation. To realize MSC potential, it is necessary to establish methods for the isolation of MSC-derived living osteoblasts. However, no osteoblast markers have been reported to date. In an attempt to develop a method for the assessment of osteoblast differentiation, we established reporter human immortalized MSC (hiMSC) lines for in vitro monitoring of bone gamma-carboxyglutamate protein (BGLAP, osteocalcin) expression. To this end, we successfully knocked-in an enhanced green fluorescent protein (EGFP) gene cassette immediately downstream of the first ATG of BGLAP via CRISPR-Cas9, and established hiMSC lines expressing EGFP to monitor osteogenic differentiation. On differentiation day 7, EGFP-positive cells were collected by flow cytometric cell sorting, and the expression of EGFP and endogenous BGLAP was analyzed. During osteogenic differentiation, EGFP upregulation was found to correlate with expression of endogenous BGLAP. Moreover, mineralization was confirmed using Alizarin red-S staining after two weeks of osteogenic differentiation of the modified hiMSC lines. The modified hiMSC lines, as well as the derived differentiated osteoblasts obtained herein, are valuable tools for the monitoring osteoblast gene and protein expression, and can be used to develop novel methods for isolating living osteoblasts. Abstract : Cell Culture; Cell Differentiation; Stem Cell Research; Cell biology; Promoter; Regenerative Medicine; bone gamma-carboxyglutamate protein; CRISPR-Cas9; mesenchymal stem cells; osteogenic differentiation; reporter cells